Comprensión lectora en estudiantes de aulas inclusivas y no inclusivas del quinto grado de primaria del Callao - Mateu Aylas, María Ernestina (2010)
The propose of the present research was to know if significant differences exist in the reading comprehension between students of inclusive and not inclusive classrooms of the Callao. I worked with two independent samples not probabilístics of 74 students each one, of 5 ° of primary, of both sex, which ages fluctuate between 10 to 12 years. The method used was the Descriptive one in a comparative Design, information has being gathered by the Test ACL proposed by Catalá (2001) and adapted by the author of the present investigation (2010) .To carry out the analysis of Validity and Hope, the information being processed with SPSS17 version in Spanish. The findings showed that doesn’t exist significant differences between the total punctuations of reading comprehension in both samples. Nevertheless in the criterial level the inclusive group to get to the top, statistically significant punctuation to the not inclusive group.